We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
66
1
avatar+160 

Question Three:

 

 Mar 3, 2019

Best Answer 

 #1
avatar+4221 
+2

Just plug in the values.

 

For A(2), we have 3-2(2)^2+4^2=11.

 

For A(1), we have 3-2(1)^2+4^1=5

 

Thus, 11-5=6.

 Mar 3, 2019
 #1
avatar+4221 
+2
Best Answer

Just plug in the values.

 

For A(2), we have 3-2(2)^2+4^2=11.

 

For A(1), we have 3-2(1)^2+4^1=5

 

Thus, 11-5=6.

tertre Mar 3, 2019

6 Online Users

avatar